Luoghi e paesaggi in Italia - Rizzo, Giulio Gino (Scuole di dottorato, 2004)
The first volume of a series connected with the Florence University PhD course in Landscape Design - a disciplinary sector that is innovative in terms of its political and social engagement - it illustrates the potential of this field of study through the results of a wide-ranging educational and creative workshop. The various design experiences are grouped into six thematic sections: Parks and landscape; City parks; Urban spaces; Fortified systems; Art sites; Historic landscapes; Concepts and projects (the latter addressing issues that are central to Italian research, such as agricultural and river landscapes).